The effect of job stress and social support on presenteeism with public service motivation as a mediator - Karmilah, Faradis; Sawitri, Hunik Sri Runing (Manajemen dan Bisnis, 2024)
The purpose of this study was to determine the effect of job stress and social support on presenteeism with public service motivation as a mediator. This study uses a quantitative approach to see the influence between variables and uses a cross-sectional approach. The population of this study were all health workers who were actively working at the Situbondo Regency Health Center at the time of the research, which amounted to 1116 health workers. The sampling technique used in this study was probability sampling with cluster sampling technique. the total sample required was 164 respondents. The results of this study are as follows: Stress challenges have a positive effect on public service motivation, Stress barriers have a negative effect on public service motivation. Supervisor support has a positive effect on public service motivation. Coworker support has a positive effect on public service motivation. Public service motivation has a positive effect on presenteeism. Public service motivation mediates the influence between challenge stress and presenteeism. Public service motivation mediates the influence between barrier stress and presenteeism. Public service motivation mediates the influence between supervisor support and presenteeism. Public service motivation mediates the influence between coworker support and presenteeism.